Diphenyl diselenide protects neuronal cells against oxidative stress and mitochondrial dysfunction : involvement of the glutathione-dependent antioxidant system - Quispe, Ruth Liliám (2019)
Oxidative stress and mitochondrial dysfunction are critical events in neurodegenerative diseases; therefore, molecules that increase cellular antioxidant defenses represent a future pharmacologic strategy to counteract such conditions. The aim of this study was to investigate the potential protective effect of (PhSe)2 on mouse hippocampal cell line (HT22) exposed to tert-BuOOH (in vitro model of oxidative stress), as well as to elucidate potential mechanisms underlying this protection. Our results showed that tert-BuOOH caused time- and concentration- dependent cytotoxicity, which was preceded by increased oxidants production and mitochondrial dysfunction. (PhSe)2 pre-incubation significantly prevented these cytotoxic events and the observed protective effects were paralleled by the upregulation of the cellular glutathione-dependent antioxidant system: (PhSe)2 increased GSH levels (> 60%), GPx activity (6.9-fold) and the mRNA expression of antioxidant enzymes Gpx1 (3.9-fold) and Gclc (2.3-fold). Of note, the cytoprotective effect of (PhSe)2 was significantly decreased when cells were treated with mercaptosuccinic acid, an inhibitor of GPx, indicating the involvement of GPx modulation in the observed protective effect. In summary, the present findings bring out a new action mechanism concerning the antioxidant properties of (PhSe)2. The observed upregulation of the glutathione-dependent antioxidant system represents a future pharmacologic possibility that goes beyond the well-known thiol-peroxidase activity of this compound.